Exploring successful implementation of occupational therapy led home fall‐hazard reduction interventions - Susan Melchert; Richard Franklin; Daniel Lowrie (Australian Occupational Therapy Journal, 2026)
Abstract Introduction Falls among older adults are a major cause of death, injury, and loss of independence. High‐certainty evidence demonstrates that comprehensive, occupational therapy–led home fall‐hazard reduction interventions can reduce the number of falls among older adults at high risk. Despite this evidence, these interventions are not routinely implemented in practice. Current literature provides limited insight into the factors that influence successful implementation of home fall‐hazard reduction interventions. This study seeks to address the following research question: ‘What influences the success of occupational therapy–led, home fall‐hazard reduction intervention implementation from the perspectives of academic and practising therapists with expertise and experience in this field?’ Methods Using a descriptive qualitative design, data were gathered via two small group interviews and one individual interview with occupational therapists experienced in implementing home fall‐hazard reduction initiatives. Participants were purposively sampled to ensure data collection from participants with relevant experience, either as an academic or practising therapist. Data were analysed using reflexive thematic analysis to identify factors influencing successful implementation. Consumer and Community Involvement There was no consumer or community involvement. Findings Five academics and four practising therapists were interviewed. Four interconnected themes were derived from the data: (1) multiple and layered measures of implementation success; (2) foregrounding falls prevention; (3) articulating a place for home fall‐hazard reduction in the falls prevention landscape; and (4) structured guidance and protocols. The interrelated nature of the themes has been illustrated in a theoretical conceptual model. Conclusion The findings suggest that attending to the multiple measures of implementation success for home fall‐hazard reduction intervention, particularly those that are context driven, may strengthen uptake across diverse practice settings. Furthermore, maximised success in implementation requires clear guidance on intervention components, improved articulation of intervention fit within the wider fall prevention landscape, and targeted support to enable occupational therapists to foreground falls prevention in practice.